A triton X-100 assisted PMAxx-qPCR assay for rapid assessment of infectious African swine fever virus - Liu, Huan; Meng, Fei; Nyaruaba, Raphael; He, Ping; Hong, Wei; Jiang, Mengwei; Liu, Dongqing; Zhou, Wenhao; Bai, Dan; Yu, Junping; Wei, Hongping (Frontiers in Microbiology, 2022)
African Swine Fever (ASF) is a highly infectious disease of pigs, caused by African swine fever virus (ASFV). The lack of vaccines and drugs makes strict disinfection practices to be one of the main measurements to curb the transmission of ASF. Therefore, it is important to assess if all viruses are inactivated after disinfection or after long time exposure in their natural conditions. Currently, the infectivity of ASFV is determined by virus isolation and culture in a biosafety level 3 (BSL-3) laboratory. However, BSL-3 laboratories are not readily available, need skilled expertise and may be time consuming. In this study, a Triton X-100 assisted PMAxx-qPCR method was developed for rapid assessment of infectious ASFV in samples. PMAxx, an improved version of propidium monoazide (PMA), can covalently cross-link with naked ASFV-DNA or DNA inside inactivated ASFV virions under assistance of 0.1% (v/v) TritonX-100, but not with ASFV-DNA inside live virions. Formation of PMAxx-DNA conjugates prevents PCR amplification, leaving only infectious virions to be detected. Under optimum conditions, the limit of detection of the PMAxx-qPCR assay was 2.32log10HAD50/mL of infectious ASFV. Testing different samples showed that the PMAxx-qPCR assay was effective to evaluate intact ASFV virions after treatment by heat or chemical disinfectants and in simulated samples such as swine tissue homogenate, swine saliva swabs, and environmental swabs. However, whole-blood and saliva need to be diluted before testing because they may inhibit the PCR reaction or the cross-linking of PMAxx with DNA. The Triton X-100 assisted PMAxx-qPCR assay took less than 3 h from sample to result, offering an easier and faster way for assessing infectious ASFV in samples from places like pig farms and pork markets.